Experience of a multidisciplinary task force with exome sequencing for Mendelian disorders. Issue 1 (December 2016) - Fokstuen, S.; Makrythanasis, P.; Hammar, E.; Guipponi, M.; Ranza, E.; Varvagiannis, K.; Santoni, F.; Albarca-Aguilera, M.; Poleggi, M.; Couchepin, F.; Brockmann, C.; Mauron, A.; et al.
Abstract Background In order to optimally integrate the use of high-throughput sequencing (HTS) as a tool in clinical diagnostics of likely monogenic disorders, we have created a multidisciplinary "Genome Clinic Task Force" at the University Hospitals of Geneva, which is composed of clinical and molecular geneticists, bioinformaticians, technicians, bioethicists, and a coordinator. Methods and results We have implemented whole exome sequencing (WES) with subsequent targeted bioinformatics analysis of gene lists for specific disorders. Clinical cases of heterogeneous Mendelian disorders that could potentially benefit from HTS are presented and discussed during the sessions of the task force. Debate concerning the interpretation of identified variants and the content of the final report constitutes a major part of the task force's work. Furthermore, issues related to bioethics, genetic counseling, quality control, and reimbursement are also addressed. Conclusions This multidisciplinary task force has enabled us to create a platform for regular exchanges between all involved experts in order to deal with the multiple complex issues related to HTS in clinical practice and to continuously improve the diagnostic use of HTS. In addition, this task force was instrumental to formally approve the reimbursement of HTS for molecular diagnosis of Mendelian disorders in Switzerland.